PENGUJIAN CEPAT VIADILITAS DENIH PINUS (Pinus merkusii) DENGAN KONTRAS RADIOGRAPHY - Jan Barlian; Decky Rinawan; , Nurhasybi (Jurnal Agronomi Indonesia (Indonesian Journal of Agronomy), 1998)
The objective of the research was to determine the best chemical for radiography contras test of pines seed viability and the key for interpretation of pines seed viability. The experiment was conducted at Seed Technology Laboratory of Forestry, Bogor from February until May 1994.           The result found the best radiography test for the pine seed with parameters for X-ray as follows, (KVp) 14 K volt voltage, (mA) 5.5 A, length of radiation (et) for 12 second, distance of focus film to object (FFD) by 25 cm, and film placed (OFD) directly above the X-ray film.           Contrast chemical BaCl2 decrease the seed viability at concentration of 30 % and soaking time for 30 minutes. Both KI and NaI decrease the viability at 10% and soaking time of 45 and 15 minutes, consequtively. Contrast chemical effectively interprete the viable and non viable seed at 10% concentration.           Viable seeds have complete structure, did not absorb the chemicals and the physical damage was less than 25% of the seed space. Non viable seeds did not have a complete structure, absorbed the chemicals and physical damage was more than 25% of the seed space